Visual Media Usage Teaching in the Special Education Integration Programme (SEIP) of Hearing Impairment in Hulu Selangor - abdul rahim razalli; noreha yusuf; rahimah kassim; nordin mamat (Department of Special Education, 2017)
This study was conducted to identify the level of usage of visual media in teaching at the Special Education Integration Programme (SEIP) Hearing Impairment. The study also identified the attitude towards the use of visual media and the limitations faced by teachers when using visual media. The findings show the use of visual media in teaching at SEIP Hearing Impairment in Hulu Selangor is in the high level and the teacher have very positive attitude towards visual media. However, the limitations faced by teachers in the use of visual media are on the high level. This research involved 50 respondents from a special education teacher who teaches in nine (9) schools of SEIP Hearing Impairment in Hulu Selangor. Questionnaires were used as research instruments and data collection was done using 5-point Likert scale. These data were processed using Software Statistical Packages For The Social Science 20. The analysis made in descriptive statistical methods in the form of frequency, percentage and mean. Results from this study indicate the level of visual media usage among teachers in SEIP Hearing Impairment are at high level (mean = 3.52), while teachers’ attitudes were very positive (mean = 4.43). There are limitations of the study showed that teachers face in SEIP of Hearing Impairment is high (mean = 3.59). Based on the findings, some suggestions are brought forward to enhance the use of visual media in teaching at SEIP Hearing Impairment